Design of SFRC members aided by a multiscale model: Part I – Predicting the post-cracking parameters - Trindade, Yasmin T.; Bitencourt Jr., Luís A.G.; Monte, Renata; de Figueiredo, Antonio D.; Manzoli, Osvaldo L. [UNESP] (Elsevier, 2020)
The use of steel fiber reinforced concrete (SFRC) is directly related to its post-cracking behavior in tension. The flexural three-point-bending test (3-PBT) according to EN 14651 is among the most recommended tests to evaluate the post-cracking parameters for application of SFRC as structural material. However, due to the intrinsic variability of the mechanical properties of this composite, its characterization using exclusively experimental tests would be very expensive and time-consuming. The present Part I of this two-part study aims to investigate the applicability of a recently proposed numerical model to obtain the post-cracking parameters of SFRC. A series of 3-PBT was experimentally performed for three different fiber contents: 15kg/m3, 30kg/m3 and 45kg/m3. These tests are simulated to study the main factors that may influence the numerical responses such as: mesh refinement; constitutive integration scheme; fiber distributions; fibers/concrete interface parameters and mesoscale vs. multiscale analysis. The results show that this strategy is able to predict the post-cracking parameters and can be applied as an aid tool, extrapolating the experimental results for better understanding the material responses. The influence of experimental and numerical post-cracking parameters on the design of beams according to fib Model Code 2010 is discussed in the accompanying Part II.
Keywords: EN 14651; Experimental tests; Numerical modeling; Post-cracking behavior; SFRC; Three-point bending test